1983
DOI: 10.1128/aac.23.6.866
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of cefoperazone in full-term and premature neonates

Abstract: The pharmacokinetics of cefoperazone were evaluated in 28 newborn infants who were being treated for sepsis. A dose of 50 mg/kg was administered intravenously on days 0 to 2 in all, with a second dose administered on days 5 to 7 in 14 hifants. Cerebrospinal fluid penetration was also studied in seven neonates. The mean peak concentration of cefoperazone in the serum of premature infants <33 weeks of gestational age, 159 (standard deviation, ±22) ,ug/ml, was higher than concentrations in premature infants 33 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
1

Year Published

1983
1983
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 7 publications
1
10
1
Order By: Relevance
“…In vivo, BMY-28142 produced significantly greater bactericidal titers in blood and CSF than did cefotaxime and penicillin G. It should be noted that the mean concentration of BMY-28142 in serum at 7 to 8 h after administration was still at approximately 14% of the 1-to 2-h level, suggesting a slow decay in vivo. This finding of presumed longer half-life is similar to half-lives observed with ceftriaxone and cefoperazone (3,11,13).…”
Section: Resultssupporting
confidence: 71%
“…In vivo, BMY-28142 produced significantly greater bactericidal titers in blood and CSF than did cefotaxime and penicillin G. It should be noted that the mean concentration of BMY-28142 in serum at 7 to 8 h after administration was still at approximately 14% of the 1-to 2-h level, suggesting a slow decay in vivo. This finding of presumed longer half-life is similar to half-lives observed with ceftriaxone and cefoperazone (3,11,13).…”
Section: Resultssupporting
confidence: 71%
“…Levels in blood during 15 to 30 min after the dose were 12 to 100 times the MIC for 90% of the strains of common pathogens, including Escherichia coli and Proteus mirabilis (9) and 17 to 30 times more than necessary to inhibit 90% of the strains of Staphylococcus aureus (9). Levels in blood observed in this study were lower than those reported in 1-to 2-day-old infants, including premature infants (11). This difference may be due to a larger dose (50 mg/kg) and also immature renal and liver functions at that age, as CPZ is excreted both by the renal and biliary tracts.…”
contrasting
confidence: 54%
“…In the pediatric age group, including neonates, the drug has not been well studied. Single doses administered during the first week of life were safe and revealed a prolonged half-life (11). We now report the pharmacokinetics of this drug in infants older than 2 weeks.…”
mentioning
confidence: 99%
“…In the preterm, t 1/2 is longer than in full-term infants as these antibiotics are mainly eliminated by renal route and the excretory renal function increases with prenatal and postnatal development. This has been observed for azlocillin [24], ticarcillin [29], cefotaxime [35], ceftazidime [42], cefoperazone [59], gentamicin [81] and amikacin [98]. Cl has a reverse trend, it is lower in preterm than in full-term infants.…”
Section: Discussionmentioning
confidence: 90%